2014
DOI: 10.15252/embj.201488143
|View full text |Cite
|
Sign up to set email alerts
|

A conformational switch in collybistin determines the differentiation of inhibitory postsynapses

Abstract: The formation of neuronal synapses and the dynamic regulation of their efficacy depend on the assembly of the postsynaptic neurotransmitter receptor apparatus. Receptor recruitment to inhibitory GABAergic and glycinergic synapses is controlled by the scaffold protein gephyrin and the adaptor protein collybistin. We derived new insights into the structure of collybistin and used these to design biochemical, cell biological, and genetic analyses of collybistin function. Our data define a collybistin-based protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
202
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(232 citation statements)
references
References 65 publications
26
202
3
1
Order By: Relevance
“…76,77 Furthermore, a recent structural study demonstrated that the collybistins can adopt open and closed conformations that act as switchable adaptors, and that NL-2 favors the open conformation by competing with a closed-conformation-favoring intramolecular interaction in collybistin. 78 The proposed functions of collybistin were demonstrated in vivo: collybistin-deficient mice displayed region-specific reductions in synaptic gephyrin clustering, reduced clustering of the GABA A receptor γ2-subunit, decreased GABAergic synaptic transmission, impaired hippocampal synaptic plasticity (i.e., increased long-term potentiation and decreased long-term depression) and impaired spatial learning. 79 Similar functional alterations were reproduced in conditional collybistin-knockout mice.…”
Section: Collybistinmentioning
confidence: 99%
“…76,77 Furthermore, a recent structural study demonstrated that the collybistins can adopt open and closed conformations that act as switchable adaptors, and that NL-2 favors the open conformation by competing with a closed-conformation-favoring intramolecular interaction in collybistin. 78 The proposed functions of collybistin were demonstrated in vivo: collybistin-deficient mice displayed region-specific reductions in synaptic gephyrin clustering, reduced clustering of the GABA A receptor γ2-subunit, decreased GABAergic synaptic transmission, impaired hippocampal synaptic plasticity (i.e., increased long-term potentiation and decreased long-term depression) and impaired spatial learning. 79 Similar functional alterations were reproduced in conditional collybistin-knockout mice.…”
Section: Collybistinmentioning
confidence: 99%
“…In particular the major variants are predicted to encode proteins that will lack or contain a candidate polyproline SH3 binding domain and the homologous region in the mammalian neuroligins harbours the binding site for gephyrin. This is pertinent because this kind of protein scaffolding domain has been implicated in dynamic regulation of neuroligin dependent synaptic differentiation of inhibitory synapses in mammals (Soykan et al, 2014). Interestingly, we observed dynamic expression of these nlg-1 variants during the development of C. elegans.…”
mentioning
confidence: 77%
“…The latter harbours a Dbl domain which has an intrinsic guanine nucleotide exchange factor activity (GEF). This activity is otherwise inhibited by an intramolecular interaction with an N terminal inhibitory SH3 domain found in most collybistin splice variants (Mayer et al, 2013;Soykan et al, 2014). This inhibition is released by ancillary binding to polyproline containing proteins, which, in the case of the gephyrin recruited collybistin, can be encoded by the SH3 binding domain that is selectively expressed by the NLGN-2 intracellular domain (Soykan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations